A one health perspective on multidrug-resistant bacterial infections: integrated approaches for surveillance, policy and innovation - Ohia, Chinenyenwa M. D.; Falodun, Olutayo Israel; Adebudo, Lucky Icomiare; Bakarey, Adeleye Solomon (Frontiers in Cellular and Infection Microbiology, 2025)
Multidrug-resistant (MDR) bacterial infections represent a growing global health emergency, driven by interconnected human, animal, and environmental factors. This review adopts a One Health perspective to explore the transmission dynamics, operational integration, and innovative responses to antimicrobial resistance (AMR). Case studies from China, India, Nigeria, Thailand, and Brazil underscore the effectiveness of regulatory reforms, surveillance networks, and public engagement campaigns. Notably, Artificial Intelligence (AI) is transforming MDR management through real-time diagnostics and resistance prediction, though ethical concerns and infrastructure deficits in Low- and Middle-Income Countries (LMICs) remain barriers. Community-led initiatives, gender-sensitive education, and policy reforms are vital to curbing misuse and closing equity gaps. Despite successes, challenges such as fragmented governance, underfunded labs, and limited longitudinal research persist. A proactive, integrated One Health approach—linking clinical, environmental, and policy actions—is essential for reducing MDR burden. Investment in intersectoral surveillance, equitable AI deployment, and community empowerment is imperative for safeguarding antibiotics and ensuring global health resilience.